Are National-Level Research Evaluation Models Valid, Credible, Useful, Cost-Effective, and Ethical? - Chris L. S. Coryn; Michael Scriven (The Evaluation Center at Western Michigan University, 2007)
The evaluation of government-financed research has become increasingly important in the last few decades in terms of increasing the quality of, and payoff from, the research that is done, reducing the cost of doing it, and lending public credibility to the manner in which research is funded. But there are very large differences throughout the world in the extent to which systems used promote these results. This paper briefly presents the dimensional results of a study designed to comparatively evaluate the national-level research evaluation models in sixteen countries on five merit-defining dimensions.